Brief Phonological Characterization of Bora - Napurí, Andrés (2015)
This work offers a quick description of the vowels and consonants of the Bora language. It also explains the linguistic and sociolinguistic criteria for the selection of graphemes in the Bora language: it highlights the importance of the written tradition for the selection of certain graphemes, such as <c> and <k> or the removal of <s> and <z>. Finally, this work discuss the presence of long vowels in the Bora language: evidence to date suggests that the Bora language has only short vowels thanks to the processes of derivation with tone in the nominal Bora lexicon